Cooperative Economy and SMEs: Strengthening Sustainable Development and Economic Resilience through Collaborative Business Models - Pramesthi, Yunesia (Lafadz Jaya Publisher, 2025)
The cooperative economy and Small and Medium Enterprises (SMEs) play a pivotal role in fostering economic resilience and sustainability, especially in emerging and developing economies. This article examines the synergy between cooperatives and SMEs, focusing on how these entities contribute to local economies, promote social inclusion, and drive community-based development. Through an analysis of case studies from various countries, this study explores the effectiveness of cooperative models in enhancing the competitiveness and sustainability of SMEs. The research highlights the role of cooperatives in providing financial support, marketing, and training to SMEs, thus empowering entrepreneurs and creating networks that foster innovation and mutual support. Moreover, the study delves into the challenges faced by cooperatives and SMEs, such as access to capital, bureaucratic hurdles, and market competition, offering recommendations for policy makers and practitioners to optimize their potential. This article also provides insights into the long-term benefits of fostering cooperative models for economic development, suggesting that cooperation between SMEs and cooperatives is not only beneficial but crucial for achieving sustainable growth in both local and global economies. The findings emphasize the importance of creating supportive environments that enhance collaboration between cooperatives, SMEs, and governments for maximizing their collective impact.